El estado protector: globalización y exclusión social. The state as protector: globalization and social exclusion - Alaminos, Antonio (Papeles del Este, 2006)
This article considers, first, some of the major typologies formulated to describe European societies. The idea proposed is to consider them in a comparative way and evaluate the degree of complementarities that exist between the different typologies and their degree of interdependence. After this overview of the different typologies, the author will next consider theories about the effects that the processes of globalization have had on said societies, especially with respect to the internationalization of consumer and labour markets. Last, some data about public opinion on globalization will be considered, as well as data on public expectations about Eastern European countries joining the European Union.